Implementasi Kode Etik Jurnalistik: Studi Kasus dikalangan Wartawan Harian Serambi Indonesia - Jufrizal Jufrizal (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Today the mass media has become one of the necessities that can not be separated from the human routines. Every moment the mass media has provided knowledge and information to the public. Increasing needs of information from public, create the mass media institutions in Indonesia developed rapidly. Each media competing to present information that attracts interest from the public. Fierce competition among institutions of mass media today sometimes make them did not work based on the several regulations that is written on the role and function of the journalist in Indonesia. Disobedience to the rules by the journalist agency workers can be seen from the violation of journalistic ethics. Journalism Code of Ethics is a set of rules in form of the Code of Conduct to which journalists practitioners are tied. It contains the principles of right and wrong and contains moral values. The purpose of this study is to determine if the Serambi Indonesia journalists understand the journalistic ethics code based on the knowledge they have, and the practical application of journalistic ethics in journalism activities among journalists of Serambi Indonesia. The results indicate that the Serambi Indonesia journalists understand and have the same understanding of journalistic ethics code as a rule of law in carrying out the task of journalism. Serambi Indonesia journalists use ethical ways when performing job as a journalist. The ethical ways include among other things: Introducing themselves as a reporter with showing a press card. At the stage of writing the news should apply the principle of covering both sides. Performing journalist duty with the independent attitude. Serambi Indonesia’s journalists gave the initials for the victim and young perpetrators of crimes. At the publication stage Serambi Indonesia is willing to give the answer rights to the reader or speaker who feel disadvantaged. ABSTRAK Dewasa ini media massa telah menjadi salah satu kebutuhan yang tidak dapat dipisahkan dari rutinitas manusia. Setiap saat media massa telah memberikan pengetahuan dan informasi kepada publik. Semakin meningkatnya kebutuhan informasi dari publik, membuat institusi media massa di Indonesia berkembang pesat. Setiap media berlomba menyajikan informasi yang menarik minat publik. Persaingan sengit antar institusi media massa saat ini terkadang membuat mereka tidak berfungsi berdasarkan beberapa regulasi yang dituliskan tentang peran dan fungsi jurnalis di Indonesia. Ketidaktaatan pada aturan oleh pekerja agen jurnalis dapat dilihat dari pelanggaran etika jurnalistik. Kode Etik Jurnalisme adalah seperangkat aturan dalam bentuk Kode Etik yang mengikat para jurnalis praktisi. Ini berisi prinsip-prinsip benar dan salah dan mengandung nilai-nilai moral. Tujuan dari penelitian ini adalah untuk mengetahui apakah jurnalis Serambi Indonesia memahami kode etik jurnalistik berdasarkan pengetahuan yang mereka miliki, dan penerapan praktis etika jurnalistik dalam kegiatan jurnalisme di kalangan jurnalis Serambi Indonesia. Hasil penelitian menunjukkan bahwa jurnalis Serambi Indonesia memahami dan memiliki pemahaman yang sama tentang kode etik jurnalistik sebagai aturan hukum dalam menjalankan tugas jurnalistik. Wartawan Serambi Indonesia menggunakan cara etis ketika melakukan pekerjaan sebagai jurnalis. Cara-cara etis itu antara lain meliputi: Memperkenalkan diri sebagai reporter dengan menunjukkan kartu pers. Pada tahap penulisan berita harus menerapkan prinsip peliputan kedua belah pihak. Melakukan tugas jurnalis dengan sikap mandiri. Wartawan Serambi Indonesia memberikan inisial untuk korban dan pelaku kejahatan muda. Pada tahap publikasi Serambi Indonesia bersedia memberikan hak jawaban kepada pembaca atau pembicara yang merasa dirugikan.